2016
DOI: 10.4172/2161-0665.1000287
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Crystalluria: A Rare Secondary Effect of a Common Drug

Abstract: Acyclovir is a highly active antiviral drug that acts against the herpes simplex virus (HSV). Among its secondary effects, we can observe rare cases of crystalluria, which can be associated or not associated to renal failure. We present the case of a healthy lactating 13-month-old baby girl with gingivostomatitis, who 48 hours after the start of treatment with this drug showed a change in the color of her urine, which was associated with the appearance of crystals in the sediment. This finding was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The case presented with gross hematuria and crystalluria was found. 15,16 AKI that occurs after a single oral dose of Valacyclovir is possible as Unsal MA et al, 17 case report in 2018. Higher doses of Valacyclovir may be safe as in Meur YL 18 correspondence followed the use of Valacyclovir 6-8 g/day in 6 cases after renal transplantation for prevention of cytomegalovirus and found that after 3 months, there was no increase in the serum creatinine and crystalluria was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…The case presented with gross hematuria and crystalluria was found. 15,16 AKI that occurs after a single oral dose of Valacyclovir is possible as Unsal MA et al, 17 case report in 2018. Higher doses of Valacyclovir may be safe as in Meur YL 18 correspondence followed the use of Valacyclovir 6-8 g/day in 6 cases after renal transplantation for prevention of cytomegalovirus and found that after 3 months, there was no increase in the serum creatinine and crystalluria was not detected.…”
Section: Discussionmentioning
confidence: 99%